SMART ENTERPRISE: THE ROLE OF DIGITAL TRANSFORMATION AND INTELLECTUAL CAPITAL IN MALAYSIAN HIGH-TECH INNOVATION - Khan, Ayesha Fatima; Chaudhry, is Iqbal (Research Journal of Economics and Sustainable Development, 2024)
This study investigates the relationship between intellectual capital and digital transformation in enhancing innovation performance in high-tech firms in Malaysia. The study adopts Partial Least Squares-Structural Equation Modelling (PLS-SEM) and relies on a structured questionnaire to collect data from 187 Malaysian Electrical and Electronics sector firms. Results indicate that the dimensions of intellectual capital (human, structural, and relational) improve the innovation performance of firms. Furthermore, digital transformation fully mediates this relationship, highlighting the critical importance of digital transformation as a key driver of firms' innovation performance. The findings offer novel insights into the role of intellectual capital and digital transformation in high-tech firms' innovation performance and suggest that policy makers and firms should pay close attention to developing intellectual capital dimensions to realize the benefits of digital transformation. The study recommends investments in both product and process innovation since they lead to better performance outcomes and can help organizations achieve competitive advantage and enhance their ability to innovate and create value for stakeholders.